2084: The End of the World by Boualem Sansal, a Voltairian dystopia (Colloquia Comparativa Litterarum, 2025)
Rooted in the dystopian tradition, 2084 : la fin du monde [2084: The End of the World] by Algerian author Boualem Sansal stands out for its inclusion of elements reminiscent of the philosophical tale, particularly Voltaire’s Candide ou l’Optimisme [Candide, or Optimism], such as the use of descriptive intertitles in the form of completive propositions, the schematic nature of the characters and the use of irony. It is this second generic affiliation that we will focus on in this article.
Keywords: Boualem Sansal; Voltaire; dystopia; philosophical tale; generic hybridity